THE ROLE OF SOCIAL MEDIA IN SHIFTING CULTURAL CHANGE (REVIEW OF LITERATURE STUDIES IN THE CONTEXT OF MEDIA AND CULTURE) - Datuk Imam Marzuki (Department of Islamic Communication and Broadcasting - Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
This article is entitled the role of social media in shifting cultural change using a qualitative research approach to literature studies. Using the Uses and Gratifications theory , namely that media use is basically determined by the individual's basic needs. The findings that arise when using social media for audiences (viewers) are: are cognitive impact, imitation impact and behavioral impact. The impact of actively using social media: first, social media can threaten the social values that exist in society. Second, social media can strengthen the social values that exist in society. Third, social media will form new social values in people's lives.